Decreased Psychological Well-Being in Patients With Bipolar Disorder in Remission. Issue 6 (10th November 2022) - Katz, Douglas; Kuperberg, Maya; Kamali, Masoud; George, Nevita; Mroczek, Daniel; Bastarache, Emily; Stephan, Nicole; Nierenberg, Andrew A.; Sylvia, Louisa
Abstract : Background: The goals of this study were to introduce psychological well-being as an important subject of inquiry in bipolar disorder, to compare well-being in a cohort of patients with bipolar disorder with that of a normative sample, and to assess whether common measures of well-being and mood measure empirically distinct phenomena. Methods: Participants were outpatients with bipolar I disorder in remission (N=37) from the Enhancing Emotion Regulation in Bipolar Disorder (EERBD) study and a matched community normative sample from the Midlife in the United States (MIDUS) survey (N=6297). The Psychological Well-Being Scale (PWBS) was used to measure psychological well-being. We calculated means and SD of scores on the PWBS and evaluated the differences between the scores of the bipolar I and community samples. We also tested the association between raw and change scores in depression [Hamilton Rating Scale for Depression (HAM-D)] and eudaimonic well-being (PWBS) using Spearman correlation coefficients. Results: The MIDUS survey sample (N=6297) was 48% male, with a mean age of 47 years (SD=13 y). The EERBD sample (N=37) was 27% male, with a mean age of 41 years (SD=11 y). In the bipolar sample, the baseline mean score on the HAM-D was 12.7 (SD=6.0) and the mean score on the Young Mania Rating Scale was 6.1 (SD=6.2). The baseline mean sum score on the PWBS in the normative community MIDUS sample was 100 (SD=14), while that of the bipolar I EERBD sample was 79 (SD=15) at baseline, 84 (SD=13) posttreatment, and 84 (SD=12) at the 3-month follow-up assessment. The effect sizes of the differences at all timepoints were large (Hedges g =1.42 at baseline, 1.11 at the end of treatment, and 1.06 at the 3-mo follow-up). No association was found between the PWBS and depression scores. Conclusions: Outpatients with bipolar disorder in remission demonstrated substantially impaired psychological well-being, despite low levels of depressive symptoms, compared with a normative community sample.